Comprehensive management of congenital choanal atresia. (July 2017) - Brihaye, Pierre; Delpierre, Isabelle; De Villé, Andrée; Johansson, Anne-Britt; Biarent, Dominique; Mansbach, Anne-Laure
Abstract: Objectives: To present results of a one-stage minimally invasive surgical procedure for congenital choanal atresia (CCA). Seven outcome measures were applied. Materials and methods: Retrospective study conducted between 1999 and 2015. The same endonasal endoscopic approach with multiflaps and no stenting was used on 36 children. The flaps were attached with fibrine glue. There were 50% unilateral and 50% bilateral cases, 70% primary and 30% secondary surgery. The mean age at primary surgery for bilateral atresia was 10 days and for unilateral atresia 4 years. Associated loco-regional disorders were: hypoplasia of the inferior turbinate, rhinopharyngeal stenosis and rhinopharyngeal web. Results: The average follow-up time was 6 years, ranging from 1 to 14 years. There was a functionally patent choanae in 94% of children, and 6% showed severe restenosis with a diameter less than 4 mm, which needed one revision surgery each. Charge patients were not associated with worse outcome. There was no external nasal valve stenosis and no permanent Eustachian tube dysfunction. Synechiae occurred in 3 patients with hyperplastic inferior turbinate. No patients showed any disharmonious nasal growth. In neonates with isolated bilateral CCA, breast-suction could be started within 1 day (range 1–2 days), and pain-killers were needed on average for 1.5 days (range 1–4 days). The hospital stay for unilateral isolated CCA was on average 1.5 days (range 1–2 days) and for bilateral isolated CCA, 8 days (range 3–20 days). Postoperative procedures under a short general anesthesia were necessary in 12 cases, 10 of them were infants under 6 months of age. Conclusion: Surgery could be performed safely in the newborn in the early stage of life, even for unilateral atresia. Tendency for restenosis can be minimized by: 1. the construction of an as large as possible uni-neochoanae by removing the posterior part of the vomer and by drilling away the medial pterygoid; 2. in case of rhinopharyngeal stenosis, part of the endochondral clivus bone should be resected; 3. all raw surfaces should be covered by multiple mucosal flaps secured with fibrin glue; 4. no stenting; 5. appropriate postoperative care.